Unmasking the Duo: Wilson's Disease in the Context of Lupus and Existing Hepatitis E Coinfection - Sana Muhammad Hussain; Anum Khan; Zahra Anas; Zarlish Khan; Amanullah Abbasi; Md Ariful Haque (Clinical Case Reports)
ABSTRACT We report the case of a 19‐year‐old woman who presented with a plethora of overlapping symptoms with complex etiology, and the final diagnosis was concurrent Wilson's disease in the background of Systemic Lupus Erythematosus and Hepatitis E infection, all of which affect similar organs and lead to a presentation with jaundice, fever, neuropsychiatric symptoms, and personality changes. In this unique case, before the manifestation o of symptoms specifically related to Wilson's disease such as bizarre behavior and initial mutism, followed by irrelevant speech, the SLE symptoms were present such as oral ulcers, alopecia, and arthralgia affecting the small joints of hands and feet along with palpitations and shortness of breath. The key clinical message is the need for thorough diagnostic evaluation, as WD can be masked or mistaken for autoimmune conditions, such as SLE. The early identification and treatment of both conditions are crucial for preventing disease progression and improving patient outcomes.